A diatom voucher flora from selected southeast rivers (USA) - Bishop, Ian W.; Esposito, Rhea M.; Tyree, Meredith; Spaulding, Sarah A. (Phytotaxa, 2017)
This flora is intended to serve as an image voucher for samples analyzed for the U.S. Geological Survey Southeast Stream Quality Assessment (SESQA). The SESQA study included measurement of watershed and water quality parameters to determine the factors that have the greatest potential to alter biotic condition. Algal samples were collected at 108 sites in 2014, from streams representing gradients in chemical and physical alteration across the southeast region. More than 375 taxa were identified during analysis for species composition and abundance. This manuscript documents the flora with light micrographs of specimens representative of their morphologic range. We define “voucher flora” as images of specimens and the names applied to those specimens for a given project. Taxonomic vouchers from federal programs have generally not been made public, yet they are a salient element of a well-documented species dataset, particularly for long-term studies. This study is part of a broader effort to improve and encourage taxonomic consistency in federal, state and local programs by accessible identification resources and inter-lab comparisons